Assessing spatial distribution of bioindicator elements in various cutaneous tumors using correlative imaging with laser-ablation-based analytical methods - Kiss, Kateřina; Kopřivová, Hana; Stejskal, Václav; Krbal, Lukáš; Buday, Jakub; Brunnbauer, Lukas; Képeš, Erik; Pořízka, Pavel; Ryška, Aleš; Kaška, Milan; Kaiser, Jozef; Limbeck, Andreas (Talanta, 2024)
Correlative imaging of cutaneous tumors provides additional information to the standard histopathologic examination. However, the joint progress in the establishment of analytical techniques, such as Laser-Induced Breakdown Spectroscopy (LIBS) and Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) in clinical practice is still limited. Their combination provides complementary information as it is also shown in our study in terms of major biotic (Ca, Mg, and P) and trace (Cu and Zn) elements. To elucidate changes in the elemental composition in tumors, we have compiled a set of malignant tumors (Squamous Cell Carcinoma, Basal Cell Carcinoma, Malignant Melanoma, and Epithelioid Angiosarcoma), one benign tumor (Pigmented Nevus) and one healthy-skin sample. The data processing was based on a methodological pipeline involving binary image registration and affine transformation. Thus, our paper brings a feasibility study of a practical methodological concept that enables us to compare LIBS and LA-ICP-MS results despite the mutual spatial distortion of original elemental images. Moreover, we also show that LIBS could be a sufficient pre-screening method even for a larger number of samples according to the speed and reproducibility of the analyses. Whereas LA-ICP-MS could serve as a ground truth and reference technique for preselected samples.
Keywords: pigmentový névus; hmotnostní spektrometrie; Humans; Lasers; bazocelulární karcinom; Carcinoma, Basal Cell; spektrální analýza; lidé; lasery; Laser Therapy; Skin Neoplasms; stopové prvky; Carcinoma, Squamous Cell; Mass Spectrometry; Melanoma; spinocelulární karcinom; Trace Elements; laserová terapie; melanom; Nevus, Pigmented; Spectrum Analysis; nádory kůže